2016
DOI: 10.1016/j.biopsycho.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Joint effects of sensory feedback and interoceptive awareness on conscious error detection: Evidence from event related brain potentials

Abstract: Error awareness has been argued to depend on sensory feedback and interoceptive awareness (IA) (Ullsperger et al., 2010). We recorded EEG while participants performed a speeded Go/No-Go task in which they signaled error commission. Visibility of the effector was manipulated, while IA was measured with a heartbeat perception task. The late Pe was larger for aware than unaware errors. The ERN was also found to be modulated by error awareness, but only when the hand was visible, suggesting that its sensitivity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…A modified version of a well-validated speeded Go/NoGo task (see Pourtois, 2010, 2012;Godefroid et al, 2016;Koban et al, 2012;Paul et al, 2017;Pourtois, 2011;Severo et al, 2017;Vocat et al, 2008) was used in the current study (see Figure 1 A for trial structure). Each trial started with the presentation of a black fixation cross lasting for 1000 ms. Then, a black arrow ('cue'), either oriented up or down, was presented.…”
Section: Experimental Task and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified version of a well-validated speeded Go/NoGo task (see Pourtois, 2010, 2012;Godefroid et al, 2016;Koban et al, 2012;Paul et al, 2017;Pourtois, 2011;Severo et al, 2017;Vocat et al, 2008) was used in the current study (see Figure 1 A for trial structure). Each trial started with the presentation of a black fixation cross lasting for 1000 ms. Then, a black arrow ('cue'), either oriented up or down, was presented.…”
Section: Experimental Task and Designmentioning
confidence: 99%
“…To this aim, we devised a factorial design where we could thoroughly explore the interplay of relevance with uncertainty during reward anticipation at the SPN level, and we eventually assessed whether these two variables showed mainly independent effects, or rather a synergistic one during this process (see Figure 1 A). To achieve this, we extracted and analyzed the SPN component from an existing ERP study by Walentowska et al (2016), in which a speeded Go/NoGo task was used (previously validated extensively across different ERP studies, Pourtois, 2010, 2012;Godefroid et al, 2016;Koban et al, 2012;Paul et al, 2017;Pourtois, 2011;Severo et al, 2017;Vocat et al, 2008). In this previous study, both the response-locked (CRN), and stimulus/feedback-locked (FRN and P3) components were carefully analyzed and reported, but not the SPN.…”
mentioning
confidence: 99%
“…IA has been shown to play a key role in the processing and regulation of emotions, with higher IA being associated with more intense feelings during emotion processing and higher activation of underlying brain regions, and better emotion regulation skills [ 16 , 17 ]. IA also contributes to other cognitive functions required for effective self-regulation such as selective attention, decision-making [ 18 ], memory [ 19 ], and error processing [ 20 22 ]. All these cognitive functions as well as emotion regulation have been reported to be disturbed in ADHD [ 23 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…IA was objectively measured by means of a well-validated heartbeat perception task [ 10 , 15 , 16 ], the Mental Tracking Method [ 41 ], in which participants are instructed to silently monitor their own cardiac activity during three separate intervals. This task is well-validated and the most frequently used task to assess interoceptive ability, which has been successfully applied in several research domains [ 10 , 16 , 18 , 22 ]. Previous research has shown that this task is sensitive to interindividual differences in IA, and sensitive enough to uncover differences in IA in other neurodevelopmental disorders (e.g., autism spectrum disorder (ASD), tic disorder) [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This in turn suggests that the different ErrP types are manifestations of similar performance monitoring systems [22][23][24][25]. Furthermore, errors, and more specifically, conscious errors, are accompanied by changes in autonomic activity, like heart rate deceleration, increase in pupil size, larger skin conductance responses and increased amygdala activity [15].…”
Section: Introductionmentioning
confidence: 99%